1990
DOI: 10.2118/18283-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Cocurrent and Countercurrent Flows in Natural Porous Media

Abstract: Summary Flow experiments involving cocurrent and countercurrent spontaneous water/oil imbibition were performed on the same laterally coated sample of a natural porous medium with local saturation measurements and various boundary conditions. The experiments with countercurrent imbibition showed slower oil recovery, a smoother water/oil front, and slightly lower ultimate oil recovery than those with predominantly cocurrent imbibition. Numerical simulations revealed that the relative permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
200
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(209 citation statements)
references
References 10 publications
8
200
0
1
Order By: Relevance
“…Although some experiments have shown that the waterflood performance in the water-wet and intermediate-wet fractured chalks may be nearly independent of wettability state (Tang and Firoozabadi, 2000), the general perception is that under favorable water-wet condition, capillary imbibition significantly improves the oil recovery (Babadagli, 2001a). An important type of capillary imbibition is the spontaneous imbibition, which involves both cocurrent and countercurrent flows in proportions depending on the ratio of gravity-to-capillary forces and on the existing conditions at the matrix boundaries (Bourbiaux and Kalaydjian, 1990). Rock properties such as matrix permeability, size and shape, wettability, heterogeneity, and boundary conditions control the capillary imbibition.…”
Section: Motivationsmentioning
confidence: 99%
“…Although some experiments have shown that the waterflood performance in the water-wet and intermediate-wet fractured chalks may be nearly independent of wettability state (Tang and Firoozabadi, 2000), the general perception is that under favorable water-wet condition, capillary imbibition significantly improves the oil recovery (Babadagli, 2001a). An important type of capillary imbibition is the spontaneous imbibition, which involves both cocurrent and countercurrent flows in proportions depending on the ratio of gravity-to-capillary forces and on the existing conditions at the matrix boundaries (Bourbiaux and Kalaydjian, 1990). Rock properties such as matrix permeability, size and shape, wettability, heterogeneity, and boundary conditions control the capillary imbibition.…”
Section: Motivationsmentioning
confidence: 99%
“…Indeed, due to capillary forces, water spontaneously invades the matrix blocks thus producing oil by countercurrent and cocurrent flows (Bourbiaux et al, 1990). However, intermediate to oil-wet field situations are often encountered in practice.…”
Section: Waterfloodmentioning
confidence: 99%
“…The matrix medium is assumed to have constant petrophysical properties throughout the bedding plane. Capillary imbibition of a matrix block involves countercurrent flows of water and oil [8] with a gradual advance of a smoothly-tilted front from the boundaries to the center of the block. The geometrical method is a simplified representation of this flow mechanism, based on the two following assumptions: -piston-type invasion of the matrix medium by displacing fluid; -a distance X of the front from block boundaries changing with time t according to a function which is independent of block shape for a given rock-fluid system.…”
Section: Equivalent Blockmentioning
confidence: 99%
“…A(X) is computed using a rapid, patented procedure for image processing. A eq (X) is a second-order polynomial: (8) Normalized area versus distance curves are discretized with a constant normalized area step to give the same weight to any volume of oil recovered independently of the time at which it is produced. The geometrical method can be applied to a stack of layers with similar petrophysical properties of the matrix medium.…”
Section: Equivalent Blockmentioning
confidence: 99%